Determinants of Early Initiation of Breastfeeding Practices of Newborns in Bangladesh: Evidence From Bangladesh Demographic and Health Survey. (October 2021) - Sakib, Md. Saifullah; Ripon Rouf, Abu Sayed Md.; Tanny, Tahmina Ferdous
Purpose: Early initiation of breastfeeding is essential for newborns after birth to reduce mortality and morbidity. Early initiation of breastfeeding awareness/activities may be a vital role in Bangladesh to minimize the infant deaths. The aim of this study is to identify factors associated with the early initiation of breastfeeding practices. Methods: In this study, Bangladesh Demographic and Health Survey (BDHS) 2017 to 2018 data was used that will be the first analysis for early initiation of breastfeeding practices in this data set in Bangladesh. Considering the importance of early breastfeeding practices, the dependent variable was divided into 3 categories (immediately: breastfeeding for less than 20 minutes, within an hour, and after 1 hour) to find a significant association with early breastfeeding practices in Bangladesh. Bivariate analysis is used to examine the differentials to early initiation of breastfeeding according to the selected number of background variables. Multinomial logistic regression is used to determine predictive independent factors associated with the dependent variable. Results: Using BDHS 2017 to 2018 data on 4950 observations, this study revealed that 24.6% of mothers breastfed their babies immediately after birth and 36.2% of mothers breastfed their babies within an hour. The rate of mothers who breastfeed their babies immediately after birth is lowest at the age of 20 to 25, mothers with a higher level of education, richer class, Khulna division, the first child born, Islam, and private/NGO. With a multivariate analysis of breastfeeding within an hour compared to immediate breastfeeding: richest (OR = 0.71), Barisal division (OR = 0.72), and Buddhism( O R = 0 . 52 ) are less likely to breastfeed newborns compared to the reference category. On the other hand, primary, secondary, and higher educated mothers are more likely to breastfeed newborns compared to no educated mothers. Besides, breastfeeding newborns after 1 hour compared to immediate after birth: mothers aged 20 to 25 (OR = 1.40), richer (OR = 1.46), higher secondary (OR = 2.06), Khulna division (OR = 1.81), and private/NGO (OR = 2.51) are more likely breastfeed newborn. Conclusion: Mother's education, wealth index, region, birth order, religion, and place of delivery have a significant impact on the early initiation of breastfeeding practices, but the rate of immediate breastfeeding is relatively lower than others. Ultimately, this information will help planners and other professionals plan strategies and interventions to provide good quality health services.